1992
DOI: 10.1902/jop.1992.63.2.100
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking in a Periodontal Practice

Abstract: This case‐control study compares the prevalence of cigarette smoking among patients in a periodontal practice (cases) with that of patients in referring general dental practices (controls). Smoking histories of patients (age ≥25 years) in a periodontal practice and five general dental practices were obtained by questionnaire. From the general practices, only patients reporting negative histories for Periodontitis were studied. Periodontal status of the periodontal practice patients was based on bone loss from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
126
1
6

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(161 citation statements)
references
References 18 publications
23
126
1
6
Order By: Relevance
“…In the study by Bakhshandeh et al, twice-daily brushing was more frequent among smokers than among nonsmokers (6). Cigarette smoking is an established risk factor for periodontal disease in healthy and diabetic patients and can be prevented through oral health promotion programs (23,32). Although alcohol consumption is not considered a risk factor for periodontal disease, it can reduce the capacity of the liver to release glucose into the bloodstream and could cause hypoglycemia (33).…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Bakhshandeh et al, twice-daily brushing was more frequent among smokers than among nonsmokers (6). Cigarette smoking is an established risk factor for periodontal disease in healthy and diabetic patients and can be prevented through oral health promotion programs (23,32). Although alcohol consumption is not considered a risk factor for periodontal disease, it can reduce the capacity of the liver to release glucose into the bloodstream and could cause hypoglycemia (33).…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional and longitudinal studies have detailed the consistent, positive association between smoking and periodontal attachment loss (Bergstrom 1989, Preber & Bergstrom 1990, Haber & Kent 1992, Horning et al 1992, Haber et al 1993, Ah et al 1994. A meta-analysis of the literature conducted by Papapanou (1996) for the 1996 World Workshop in Periodontics revealed that smokers have an almost 3-fold increase in their risk for severe periodontal disease vs non-smokers.…”
Section: Introductionmentioning
confidence: 99%
“…This was similar to the study done by Arno et al, [10] who also found the relationship between increased consumption of smoking and periodontal destruction. Haber & Kent [11] found that there were a higher percentage of current and former smokers with advanced periodontal destruction. Our study was inaccordance with the study done by Grossi et al, [12] who reported that the risk of having periodontitis was 2.05 times greater in moderate smokers and 4.75 times greater in heavy smokers than nonsmokers.…”
Section: Discussionmentioning
confidence: 99%